Direct Democracy and Resource Allocation Experimental Evidence from Afghanistan - Beath, Andrew (The World Bank, 2012)
Direct democracy is designed to better align public resource allocation decisions with citizen preferences. Using a randomized field experiment in 250 villages across Afghanistan, this paper compares outcomes of secret-ballot referenda with those of consultation meetings, which adhere to customary decision-making practices. Elites are found to exert influence over meeting outcomes, but not over referenda outcomes, which are driven primarily by citizen preferences. Referenda are also found to improve public satisfaction, whereas elite domination of allocation processes has a negative effect. The results indicate that the use of direct democracy in public resource allocation results in more legitimate outcomes than those produced by customary processes